Analysis of Caffeine Levels in Pacitan Speciality Coffee Using UV-Visible spectrophotometry - Efendi, Yahya; Myesha A, Renetha Salma; Syahnuron, Fathur (TIME in Physics, 2025)
The Indonesian community, particularly the people of Pacitan Regency, has a deep-rooted connection with coffee. Coffee is a beverage that is almost always served to guests as a customary offering. Pacitan Regency is known for its unique local coffee varieties, namely Kopi Tejo, Kopi Klethik, and Kopi Bima. Coffee contains caffeine, a group of methylxanthine compounds that occur naturally and are classified as xanthine derivatives, belonging to the alkaloid compound group. Caffeine in coffee provides various health benefits when consumed in moderate amounts. This study aimed to analyze the caffeine content in Pacitan’s traditional coffee varieties using UV-Visible spectrophotometry. The analysis revealed that Kopi Tejo contains 0.6040 mg of caffeine per gram, Kopi Klethik contains 0.5547 mg of caffeine per gram, and Kopi Bima contains 0.3213 mg of caffeine per gram.